Progression to Critical Illness and Death in Patients With Breakthrough Hospitalizations - Suleyman, Geehan; Fadel, Raef; Alsaadi, Ayman; Sueng, Luis Ng; Ghandour, Ali; Alkhatib, Ahmad; Singh, Tarandeep; Parsons, Austin; Miller, Joseph; Ramesh, Mayur; Brar, Indira; Alangaden, George (Open forum infectious diseases, 2022)
Abstract Background Characterization of disease progression and outcomes after coronavirus disease 2019 (COVID-19)–related hospitalization in vaccinated compared with unvaccinated individuals is limited. Methods This was a retrospective case–control study of symptomatic vaccinated (cases) and unvaccinated (controls) participants hospitalized for COVID-19 between December 30, 2020, and September 30, 2021, in Southeast Michigan. Hospitalized adult patients with lab-confirmed COVID-19 were identified through daily census report. Breakthrough infection was defined as detection of severe acute respiratory syndrome coronavirus 2 ≥14 days after completion of the primary vaccination series. The association between prior vaccination and critical COVID-19 illness (composite of intensive care unit [ICU] admission, invasive mechanical ventilation [IMV], 28-day mortality) was examined. Results Two hundred ten (39%) fully vaccinated and 325 (61%) unvaccinated patients were evaluated. Compared with controls, cases were older, had more comorbidities (4 [3–7] vs 2 [1–4]; P < .001), and were more likely to be immunocompromised. Cases had less severe symptoms compared with controls (2 [1–2] vs 2 [2–3]; P < .001) and were less likely to progress to critical COVID-19 illness (33.3% vs 45.5%; P < .001); 28-day mortality was significantly lower in cases (11.0% vs 24.9%; P < .001). Symptom severity (odds ratio [OR], 2.59; 95% CI, 1.61–4.16; P < .001) and modified Sequential Organ Failure Assessment score on presentation (OR, 1.74; 95% CI, 1.48–2.06; P < .001) were independently associated with development of critical COVID-19 illness. Prior vaccination (OR, 0.528; 95% CI, 0.307–0.910; P = .020) was protective. Conclusions COVID-19-vaccinated patients were less likely to develop critical COVID-19 illness and more likely to survive. Disease severity at presentation was a predictor of adverse outcomes regardless of vaccination status.